Economic Integration, Foreign Direct Investment And Growth In ASEAN Five Members - Yew, Siew Yong (2007)

(untitled)
This study examines the effects of economic integration on FDI flows and the effects of FDI flows on economic growth in ASEAN5 countries. ASEAN, as an RTA is facing economic threats from China and India and other RTAs. Individually, the economies of ASEAN are small. To face the threats, ASEAN need to integrate economically to form a larger market size and functionally to facilitate the attraction of capital inflows to achieve medium and long run growth in the hub and spillover effects in the peripheral countries. The study applies panel data techniques (unit root and cointegration tests) on annual data from Indonesia, Malaysia, Philippines, Thailand and Singapore over the period from 1970 to 2005. After confirming the stationarity and long-run relationships, we applied the Pedroni’s FMOLS method to estimate the variable coefficients. We found market size, economic integration, human capital, infrastructure and existing FDI stock to be robustly significant (1%) to FDI for ASEAN5. We also found that FDI economic integration and human capital to be robustly significant (1%) to economic growth, manufacturing sector growth and high technology sector growth for ASEAN5. The FDI flowing into ASEAN5 was found to be market seeking in nature while human capital was found to be inversely proportional to the per capita income of the five countries. The high level of elasticity of existing FDI stock on FDI inflows suggest the existence of bottlenecks or saturation of FDI inflows arising from sectoral bias. The effect of FDI on economic growth of ASEAN5 countries was found to be higher for countries with higher per capita income. At the same time, the human capital variable was found to be higher in elasticity as the growth variable move from economic growth to manufacturing growth to high technology growth. Coupled with strong intra-industry trade in the manufacturing sector of ASEAN5, an integrated approach to draw in FDI and promote manufacturing and high technology growth should be accelerated. The machinery and electrical appliances industry contributes the highest trade in the region and is highly integrated in intra-industry trade within the region. The key hubs of the industry within the region are Malaysia and Singapore. From the robust significance of integration level, human capital, FDI inflows and growth, an integrated open liberalization approach must be adopted with particular focus on human capital development, for ASEAN5 to meet the challenges ahead.